In situ photodegradation of incorporated polyanion does not alter prion infectivity. - Justin R Piro; Brent T Harris; Surachai Supattapone (PLoS Pathogens, 2011)
Single-stranded polyanions ≥40 bases in length facilitate the formation of hamster scrapie prions in vitro, and polyanions co-localize with PrP(Sc) aggregates in vivo. To test the hypothesis that intact polyanionic molecules might serve as a structural backbone essential for maintaining the infectious conformation(s) of PrP(Sc), we produced synthetic prions using a photocleavable, 100-base oligonucleotide (PC-oligo). In serial Protein Misfolding Cyclic Amplification (sPMCA) reactions using purified PrP(C) substrate, PC-oligo was incorporated into physical complexes with PrP(Sc) molecules that were resistant to benzonase digestion. Exposure of these nuclease-resistant prion complexes to long wave ultraviolet light (315 nm) induced degradation of PC-oligo into 5 base fragments. Light-induced photolysis of incorporated PC-oligo did not alter the infectivity of in vitro-generated prions, as determined by bioassay in hamsters and brain homogenate sPMCA assays. Neuropathological analysis also revealed no significant differences in the neurotropism of prions containing intact versus degraded PC-oligo. These results show that polyanions >5 bases in length are not required for maintaining the infectious properties of in vitro-generated scrapie prions, and indicate that such properties are maintained either by short polyanion remnants, other co-purified cofactors, or by PrP(Sc) molecules alone.